2007 IEEE Intelligence and Security Informatics 2007
DOI: 10.1109/isi.2007.379524
|View full text |Cite
|
Sign up to set email alerts
|

Relationally Mapping XML Queries For Scalable XML Search

Abstract: The growing trend of using XML to share security In Fig. 1, we show the total query time for each query. Also data requires scalable technology to effectively manage the shown are the mean and total times for each run. All timings volume and variety of data. Although a wide variety of methods given represent the average execution time of the queries (in exist for storing and searching XML, the two most common gvn rere the average exeut e of the q eries techniques are conventional tree-based approaches and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although the conclusion of this study showed linear execution time for eXist, the collections used were not large enough to draw reliable conclusions about the scalability of eXist on modern, real-world collections. Similarly, the SQLGenerator performed initial scalability studies by running a wide range of XML queries on increasingly large collections ranging in size from 500 MB to 8 GB [15].…”
Section: Enginesmentioning
confidence: 99%
“…Although the conclusion of this study showed linear execution time for eXist, the collections used were not large enough to draw reliable conclusions about the scalability of eXist on modern, real-world collections. Similarly, the SQLGenerator performed initial scalability studies by running a wide range of XML queries on increasingly large collections ranging in size from 500 MB to 8 GB [15].…”
Section: Enginesmentioning
confidence: 99%